The Role of Ge'ez in Shaping Ethiopian Intellectual Traditions: Contributions to Science, Medicine, Astronomy, Religion, Culture, and Mathematical Thought - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2025)
Ge'ez, one of the world’s oldest written languages, has shaped Ethiopia’s intellectual heritage since the Aksumite Kingdom, serving as the liturgical language of the Ethiopian Orthodox Tewahedo Church and a medium for preserving knowledge across disciplines (Ullendorff, 1968). This study investigates Ge'ez’s contributions to science, traditional medicine, astronomy, religion, culture, and mathematical thought, emphasizing its role in Ethiopia’s development. Qualitative content analysis was conducted on 65 Ge'ez manuscripts from the Institute of Ethiopian Studies and digitized collections, supplemented by 12 semi-structured interviews with clergy and scholars. Thematic analysis identified Ge'ez’s impact across disciplines. Ge'ez preserved philosophical treatises, medical remedies, astronomical calculations, and religious texts, including the unique Ge'ez Bible. It facilitated cultural preservation through illuminated manuscripts and supported practical mathematics. Challenges included limited manuscript access and translation barriers. Ge'ez was instrumental in sustaining Ethiopia’s intellectual and cultural traditions, particularly within the Ethiopian Orthodox Tewahedo Church, positioning it as a vital component of African scholarship. Establish Ge'ez research centers, digitize manuscripts, integrate Ge'ez into curricula, and promote its global recognition through UNESCO and cultural programs.